AUTOMATION BASED ON ROBOTICS (Multidisciplinary Journal of Science and Technology, 2024)
Robotics and automation occupy an important place among modern technologies, causing revolutionary changes in such fields as production, agriculture, health care, and services. In this article, the main concepts, advantages and areas of application of automation based on robotics are considered. It is emphasized that with the help of robotics, it is possible to achieve achievements such as increasing productivity, improving product quality, reducing costs and ensuring human safety. The paper also discusses future prospects, including new advances in the field of artificial intelligence and learning robots, social and service robots, and nanorobots. By using these technologies, the possibilities of achieving sustainable development in various fields and making human life more comfortable and safe will be illuminated.